Spontaneous resolution of superficial temporal artery pseudoaneurysm. Issue 11 (30th November 2022) - Raskin, Jonathan; Pak, Kaitlynne; Lee, Matthew Kun
Abstract : Superficial temporal artery (STA) pseudoaneurysms are rare vascular lesions that typically present after traumatic head injury. Currently, surgery is the recommended treatment as spontaneous resolution has not been previously reported. Our study aims to present a review of the literature on STA pseudoaneurysms and report a case of spontaneous resolution of a traumatic STA pseudoaneurysm without the need for direct intervention.